Temperature and moisture effects on the failure of composites - Lua, Jian Wei (2017)
Composites are gaining popularity in their usage due to their exception mechanical properties. In recent years, composites are viewed as the next generation materials in the aerospace and marine industries. This project investigates the properties of the unidirectional carbon fiber reinforced polymer (CFRP) fabricated using Gurit Prime 20 resin and T300 Carbon fibers via the Vacuum Assisted Resin Transfer Method (VARTM). The samples will also be subjected to environmental conditioning by immersing it in seawater at 60°C for 30 days. Static 3-point bending test was done on both wet and dry samples to examine the effects on the flexural properties. A significant 33.65% reduction in the flexural strength was recorded upon the conditioning of the samples. This deterioration could be explained by the plasticization effect on the matrix due to the immersion of samples in seawater. Large scatter and huge deviation were also observed in the experimental data of the flexural strength. The 2-parameter Weibull distribution was found to be a suitable fit for the flexural strength data for the set of 16 dry samples. Scanning Electron Microscope (SEM) was used to examine the damage of the composite. Breakage of fibers and delamination were identified as the failure mechanism in the CFRP samples. In addition, traces of salt could be found in samples which undergo the seawater immersion conditioning.